2015
DOI: 10.12968/denu.2015.42.10.939
|View full text |Cite
|
Sign up to set email alerts
|

An overview of preformed metal crowns part 2: the hall technique

Abstract: Part 2 of this series of two articles addresses the Hall Technique for preformed metal crowns. It will discuss the need for an effective child and dentist friendly method to restore carious primary molars. The technique is described in detail and the evidence for its effectiveness and acceptance by children, parents, dentists and dental educators is presented. CPD/Clinical Relevance: Dentists and dental care professionals should be aware of the evidence to support the adoption of the Hall Technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…This will help in saving lot of financial resources and avoiding unnecessary use of sedation and general anesthesia in children. 9 conclusIon Within the limitation of the present systematic review, it can be concluded that Hall technique is a not only a predictable restorative option but it has significantly outperformed the conventional method of treatment of carious primary molars. The success rate of Hall technique is 5 times that of the conventional restorative techniques.…”
Section: Yesmentioning
confidence: 70%
“…This will help in saving lot of financial resources and avoiding unnecessary use of sedation and general anesthesia in children. 9 conclusIon Within the limitation of the present systematic review, it can be concluded that Hall technique is a not only a predictable restorative option but it has significantly outperformed the conventional method of treatment of carious primary molars. The success rate of Hall technique is 5 times that of the conventional restorative techniques.…”
Section: Yesmentioning
confidence: 70%
“…Also, evidence shows the significant effect of restoration of caries on the growth and development of children and their psychological well-being [27,2931]. SSCs are extensively used for restoration of primary molars [9,32, 33]. Selection of a crown that efficiently covers all dental surfaces and provides adequate occlusion is important for the reconstruction of severely carious primary teeth.…”
Section: Discussionmentioning
confidence: 99%
“…A técnica de Hall utilizando coroa metálica, é baseada no conceito biológico da lesão de cárie dentária que consiste na criação de uma barreira entre o meio oral e a lesão cariosa, sem que haja um desgaste do dente a ser reabilitado e sem que se remova a dentina cariada (HYDE et al,2015). A técnica foi desenvolvida pela Dra.…”
Section: Hall Techniqueunclassified